The Blessed Land: Internalization of Past Disaster into Culture by Sangihes Coastal Community - Christian, Yoppie; Desmiwati, Desmiwati; Damar, Ario (TDMRC, Universitas Syiah Kuala, 2020)
This paper explores how the coastal community of Sangihe Island, North Sulawesi, Indonesia adapted from past disasters through internalization of bad memories. To build an understanding of the cultural construction of this adaptation, this paper uses a cultural ecology framework and information collected through phenomenological study to identify the primary socio-historical information derived from past disasters. The results of the research show that the community has internalized the memories of disaster through material and non-material culture, as well as spatial arrangements of infrastructure to address the multiple threats of volcanic eruption, tsunami and typhoon risks, witnessed by their ancestors. This paper shows that the communities of Sangihe apply embedded knowledge and experience into daily practices. This is one of the models of indigenous knowledge-based disaster risk reduction, which can be a foundation for the present generations outside Sangihe to minimize the impact of disasters.